Application of nanoparticle-immobilized thermostable β-glucosidase for improving the sugarcane juice properties. (February 2016) - Agrawal, Ruchi; Verma, A.K.; Satlewal, Alok
Abstract: β-glucosidases are among the key enzymes for juice and beverage industries. They are responsible for the release of aromatic compounds in fruits and fermentation products. In this study, β-glucosidase was isolated, purified, and characterized from an indigenously developed Bacillus subtilis mutant PS-5CM-UM3. It is a 56 kDa protein monomer (isoelectric point of 5.6) belonging to 1 glycosyl hydrolase family. The purified β-glucosidase was immobilized on SiO2 nanoparticles (with 52% efficiency and 14.1% yield) to improve the thermostability and Michaelis constant (Km ) value of β-glucosidase from 0.9 to 1.1 mM. The immobilized enzyme showed improved storage stability and was reusable for up to 10 cycles with 70% residual activity. β-glucosidase treatment in sugarcane juice elevated the phenolics content with about 2.6 folds and 2.4 folds increase in p-hydroxy benzoic acid (PHBA) and gallic acid, respectively. The results show that recyclable immobilized enzyme system is a novel green approach for improving the sugarcane juice properties. Industrial relevance: In this study, β-glucosidase originally isolated and purified from an indigenously developed Bacillus subtilis mutant was immobilized on SiO2 nanoparticles. The immobilization has improved the thermostability, storage stability, and Michaelis constant (Km ) value of the β-glucosidase. The immobilized β-glucosidase is now reusable for 10 cycles with 70% residual activity. Further, β-glucosidase treatment in sugarcane juice elevated the phenolics content with about 2.6 folds and 2.4 folds increase in p-hydroxy benzoic acid (PHBA) and gallic acid, respectively. Hence, this study provides a green and sustainable approach for the food industry to efficiently enhance the juice properties. Highlights: Isolation, purification, and characterization of β-glucosidase. Enhanced thermostability of β-glucosidase (60–70 °C) by immobilization on SiO2 nanoparticles. Recycling of immobilized β-glucosidases without significant activity loss. Treatment of sugarcane juice with β-glucosidase enhanced the phenolics concentration by > 2 folds as compared to the control.